Post-marketing surveillance study to assess the safety and tolerability of an Inactivated Poliomyelitis Vaccine in Indian children - Hitt Sharma; Rajeev Dhere; Sameer Parekh; Sunil Shewale (Human Vaccines & Immunotherapeutics, 2017)
Objective: To evaluate the incidence of adverse events following administration of an Inactivated poliomyelitis vaccine (IPV) manufactured by Serum Institute of India Pvt. Ltd., Pune, India. Methods: A single 0.5 ml dose of the IPV was administered intramuscularly to children attending private clinics or out-patient department of hospitals for routine immunization across different cities in India. They were observed over a period of 30 d for local or systemic adverse events and rare case of anaphylaxis, if any. Results: A total of 2210 children were enrolled of which 2120 children received the vaccine within primary immunization series and 90 children received booster dose. The common adverse events reported were pain, erythema, swelling and fever. No serious adverse event was reported during the study period. Conclusions: Poliomyelitis vaccine (Inactivated) manufactured by Serum Institute of India Pvt. Ltd., Pune can be safely administered to children following the Expanded Programme on Immunization or World Health Organization recommended immunization schedule.